A bibliometric study of the top 100 most-cited papers in neuroendocrine prostate cancer - Gan, Yu; He, Qiangrong; Li, Chao; Alsharafi, Bassam Lutf Mohammed; Zhou, Hengfeng; Long, Zhi (Frontiers in Oncology, 2023)
Background: This study used bibliometrics to define and analyze the characteristics of the first 100 most cited papers on the topic of neuroendocrine prostate cancer (NEPC). Methods: We explored the Web of Science Core Collection database, and screened the top 100 most frequently cited articles and reviews with the title NEPC or small cell prostate cancer (SCPC). We conducted bibliometrics research on the screening results to identify the most influential journals and authors in the field of NEPC. Results: The first 100 most cited papers have been cited a total of 14,795 times, from 73 to 833 times (mean ±standard deviation, 147.95±101.68). All top 100 most cited papers were published from 1984 to 2019, and the total number of citations for papers published in 2016 was significantly higher than that for papers published in other years. The journal with the largest number of published papers is “Prostate” (n=8). “Neuroendocrine differentiation” has become the most frequently used author keyword. “Oncology” is the most popular topic in the field of NEPC. Conclusion: We analyzed the first 100 most cited papers in the NEPC field by collecting detailed information, which provide guiding opinions for finding the most influential journals and authors in NEPC-related fields. We hope to help researchers and readers in this field improve their understanding of NEPC research trends and provide ideas for future research from a unique perspective.